Oedipus - detective and psychoanalyst? - Rosenfield (UFRGS), Kathrin H. (ANTARES: Letras e Humanidades, 2010)
This article analyzes the Prologue of Oedipus Rex, highlighting not only the plot of the self-recognition of Oedipus (in search of himself). What is at stake objectively speaking in this play? Is there not a realistic level of meaning on which Oedipus' subtle ears detect unsettling signs of real plotting in the behavior of the other characters of the play (Creon and Jocasta mainly)? In this perspective, the oracle my be considered by Oedipus as a means of investigating Creon's thoughts, memories and deductions - rather than as a revelation of divine truth. This first scene introduces the reader into the discovery of a real detective story, which is part of the famous tragedy.